2019
DOI: 10.1097/inf.0000000000002343
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Systemic Inflammation in Ugandan Infants and Children Hospitalized With Respiratory Syncytial Virus Infection

Abstract: Background: Optimizing outcomes in Respiratory Syncytial Virus (RSV) pneumonia requires accurate diagnosis and determination of severity that, in resource-limited settings, is often based on clinical assessment alone. We describe host inflammatory biomarkers and clinical outcomes among children hospitalized with RSV lower respiratory tract infection (LRTI) in Uganda and controls with rhinovirus and pneumococcal pneumonia. Methods: 58 children hospitalized with LRTI were included. We compared 37 patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…TNC is reported to be a extracellular proinflammatory factor that responses to virus infection [27,28] and associated with lung organogenesis [29]. LCN2, known as neutrophil gelatinase-associated lipocalin, is an attractive biomarker of inflammation and virus infection [30][31][32]. CHI3L1 plays a critical role in multiple virus-induced airway inflammation and could be a potential therapeutic candidate for attenuating Th2-associated immunopathology [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNC is reported to be a extracellular proinflammatory factor that responses to virus infection [27,28] and associated with lung organogenesis [29]. LCN2, known as neutrophil gelatinase-associated lipocalin, is an attractive biomarker of inflammation and virus infection [30][31][32]. CHI3L1 plays a critical role in multiple virus-induced airway inflammation and could be a potential therapeutic candidate for attenuating Th2-associated immunopathology [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…LCN2, known as neutrophil gelatinase-associated lipocalin, is an attractive biomarker of inflammation and virus infection [30][31][32]. CHI3L1 plays a critical role in multiple virus-induced airway inflammation and could be a potential therapeutic candidate for attenuating Th2-associated immunopathology [32][33][34][35]. LTF has a host-protective effect against virus infection through inhibiting the attachment of a virus to the cells, replication of the virus in the cells, and enhancement of systemic immune functions [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A subset of upregulated proteins is secretory including S100A12, S100A8, S100A9, SERPINB3, DEFA3, LCN2 and TXN. LCN2, which came up in our study was previously shown to be an important biomarker for viral infection (72,73), and was also reported to be upregulated in transcriptomic and proteomic studies in COVID-19 patients (74,75). It has been shown that virus replication and inflammation goes down when thioredoxin reductase, a reducing agent of TXN is inhibited using auranofin, pointing towards the importance of redox environment during SARS-CoV2 pathogenesis (76), akin to many inflammatory responses which are governed by the redox status of the cell (77).…”
Section: Discussionmentioning
confidence: 55%
“…However, Warszawska et al (2013) report that LCN2 deactivates macrophages through an IL-10/STAT3-dependent mechanism and worsens pneumococcal pneumonia outcomes, which may be due to differences cell subset and bacterial strain. Besides, LCN2 can be as a biomarker of systemic inflammation in infants hospitalized with respiratory syncytial virus (RSV) infection ( Sawatzky et al, 2019 ) and as a biomarker of inflammation, monocyte activation, and cardiac stretch during activation of the renin-angiotensin-aldosterone system in human immunodeficiency virus ( Bogorodskaya et al, 2019 ). In this study, we found that neutrophil is one of the main drivers of inflammatory response after virus infection.…”
Section: Discussionmentioning
confidence: 99%